Santa Muerte, a védelmező Halál kultusza Mexikóban - Belovári, Anita (Acta Scientiarum Socialium, 2015)
Santa Muerte, the Cult of Protective Death in Mexico The purpose of this paper is to analyze the rapidly growing cult of the unofficial Mexican folk saint Santa Muerte. She looks like the Grim Reaper: she wears a robe and hood and holds a scythe and globe in her hands. Santa Muerte is the female personification of death itself. In the eye of the public, she is the patron saint of drug cartels, because of her portrayal in the media. But the majority of her devotees are not cartel members. They are housewives, police officers, taxi drivers, lawyers, doctors, businessmen, street dealers, etc. More than 5 million people on both sides of the Mexican–USA border. However the Catholic Church rejects the cult of the skeleton saint. She is very controversial and very versatile, protects the deceived women, LGBT people, prostitutes and others of whom the Catholic Church does not approve. She has a rich European and pre-Christian history, but what is her future?
Keywords: popular religion; cult; folk saint; death; drogcartels